PENGARUH KOMPENSASI TERHADAP KINERJA PEGAWAI PENGADILAN AGAMA KABUPATEN SINJAI - Asrul; Siti Hasbiah; Romansyah Sahabuddin; Burhanuddin; Uhud Darmawan Natsir (Lafadz Jaya Publisher, 2023)
This study aims to determine the effect of compensation on the performance of employees of the Sinjai District Religious Court. The variable in this study is Public Governance. The population in this study were all employees of the Sinjai District Religious Court, while the sample used was 30 employees. Data collection techniques were carried out using a questionnaire. Data analysis techniques were carried out using qualitative descriptive analysis which was used to describe how compensation influences the performance of religious court employees in Sinjai Regency. Data obtained from research results will be compared between theory and data obtained from research. The results of this study indicate that compensation has a good effect on the performance of religious court employees in Sinjai Regency. , increasing the welfare of employees by providing health benefits, old age benefits, pension funds, work accidents, the amount of income and benefits given according to achievement or level of success of the individual or group has predetermined success criteria.